Magmatismo há ca. 660 - 640 Ma no Domínio Socorro: Registros de convergência-colisional na Aglutinação do Gondwana Ocidental - Hackspacher, Peter Christian [UNESP]; Fetter, Allen Hutcheson [UNESP]; Ebert, Hans Dirk [UNESP]; Janasi, Valdecir de Assis; Dantas, Elton Luiz; de Oliveira, Marcos Aurélio Farias [UNESP]; Braga, Iramaia Furtado [UNESP]; Negri, Francisco de Assis (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2003)
Uranium-lead zircon ages between 660 and 640 Ma, obtained from a series of calc-alkaline orthogneisses and plutons in southeast Brazil's Central Mantiqueira Province, suggest that a significant period of magmatism occurred in this region prior to the collisional assembly of West Gondwana (presently constrained in the region between ca. 625 and 580 Ma). While the nature of this earlier magmatism is presently unclear, some preliminary Sm-Nd data suggest that these magmas were not solely derived from the Paleoproterozoic lithosphere, but appear to represent hybrid products of Paleoproterozoic and Neoproterozoic sources. As such hybrid mixtures have been most commonly observed in continental are settings, it is possible that the 660 to 640 Ma magmatism represents are magmatism that resulted from subduction of Neoproterozoic oceanic crust during early precollisional convergence and closure of a branch of either the Adamastor or Goianides oceans.
Magmatism between ca. 625 - 580 Ma in the Socorro domain: Representing a precollisional convergence of West Gondwana
Keywords: Mantiqueira province; Neoproterozoic; Precollisional convergence; geochronology; Gondwana; magmatism; plate convergence; Proterozoic; samarium-neodymium dating; Brazil